Pengaruh Total Resistance Terhadap Produktivitas Dump Truck Komatsu HD 785-7 di Area IUP 329 Ha PT. Semen Padang - Ade Fikri; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2023)
PT. Semen Padang is a company that focuses on the cement industry with locations in Indarung, West Sumatra. One of the natural resources needed is limestone as a raw material for making cement. This study conducted a comparative analysis of productivity with fuel consumption used against working hours. The analysis carried out is to look at the effect of productivity on dump truck fuel. The transportation equipment used in this study is the Dump Truck Komatsu HD-785 with the hauling distance from PNBP 6 to Crusher VI of 1.23 km with an average road slope of 11.2% and along with such productivity targets will certainly affect material consumption. fuel, so that with a longer travel time will result in greater fuel use. This research was conducted on the productivity process with the aim of optimizing the productivity of the transportation equipment, obtaining a lower fuel ratio value, and using fuel for the Komatsu HD-785-7 transportation equipment to achieve productivity targets.